Effects of Salt and Nitrogen Treatments on End Use Quality in Different End Use Types of Wheat - Jennifer N. Bragg; Jiping Liu; Matthew J. Milner (Plants)
Farmers frequently rely on mineral fertilizers to increase yields, improve or sustain crop productivity, and mitigate the adverse impacts of environmental stresses, including salinity. However, improper fertilization—whether inadequate or excessive—can hinder plant growth, reduce nutritional quality, and contribute to soil degradation and environmental pollution. Understanding how different levels of nitrogen (N) fertilizers and abiotic stresses such as salt impact yields and end-use quality is important to maintain food production and ensure fair crop value. In this study, we examined four types of spring wheat to investigate the role of adequate N levels in salt tolerance and their effects on end-use quality. The findings revealed no uniform response to either low N or salt treatment regarding growth or grain characteristics. All aspects, including biomass reduction, yield response variations, and grain components such as protein content, starch, or fiber, were influenced by different abiotic stresses across the various backgrounds tested. In some cases, these stresses were additive, further reducing crop value in specific genetic backgrounds, while, in others, their effects were minor. We identified varieties that are relatively tolerant to lower N levels, maintaining both yields and biomass production, as well as varieties that are less sensitive to salt, allowing them to sustain yields and biomass production. This deeper understanding of these varieties can now be leveraged to breed for improved stress tolerance across the entire life cycle, further enhancing yields under suboptimal conditions and minimizing the effects of reduced N inputs and salt tolerance.